Urf Terhadap Tradisi Ganti Kemul di Desa Kebondalem Kec. Bangorejo Kab. Banyuwangi, Institut Sunan Giri Ponorogo. - Lia Duwi Azizah; Kadenun Kadenun; Diyan Putri Ayu (Institut Agama Islam Sunan Giri Ponorogo, 2023)
Abstract; There is in Kebondalem Village a tradition of Changing Kemul which is stiil being carried out by the people in the area there until now. The tradition of changing kemul is one of the traditions which is carried out after or at the thusandth day of the person who died, which is intended for. The deceased in the tradition of changing kemul there are several rituals that are carried out, namely in the form of offerings and sanding, and there are several other requirements. Therefore, the researcher will describe how the tradition of changing kemul is practiced in Kebondalem village? And how is ‘urfs review of the tradition of changing kemul? In order to provide additional insight regarding the legal basis as a reason for the survival of a tradition, which is not only due to following what is already in effect in society. In this study, the researcher used a gualitative descrptive research type which had primary and secondary data sources, with the existence of techniques in extracting data by way of direct and indirect interviews, as well as documentation. The results of this study revealed to the researcher that, regarding the practice of the chang kemul tradition in Kebondalem village, it belongs to the urf al-Am group in terms of urf al-Khas, in terms of its validity it belongs to the type of urf which is Sahih. Because in the sense that urf, which belongs to the tradition of changing kemul, does not conflict with texts or hadiths, and also does not bring harm to the people of that area.